Repairing Electrical Power Imbalances on the MDP Panel for Operational Reliability at State Vocational School 1 Stabat - Muhammad Ady Pratama; Haris Gunawan; Parlin Siagian (Sean Institute, 2026)
Power imbalance in a three-phase system is a critical issue that can disrupt the operational reliability of equipment, particularly in installations such as SMK Negeri 1 Stabat. This problem was identified in the Main Distribution Panel (MDP) which showed an imbalance in the load between phases (R, S, and T), which caused an increase in the current flowing in the neutral conductor. Current measurements conducted over five days showed a high percentage of imbalance, especially during the day (peak operating hours), with the highest value reaching 26.24% on Tuesday afternoon, far exceeding the ideal limit (generally <10%). The impact of this imbalance is power losses, increased temperatures in cables and transformers, and potential equipment damage. To overcome this problem and improve the reliability of the system, three main improvement solutions were implemented: (1) Replacing the input cable from MDP to several SDPs from 4x16mm² to 3x50mm² + N to adjust the load, (2) Repairing the cable lugs in the SDP panels that were corroded or loose to eliminate voltage losses, and (3) Increasing the school's electrical power from 53 Kva (MCCB 80A) to 66 Kva (MCCB 100A). The implementation of this solution succeeded in reducing the trip frequency on the main MCCB and increasing the operational reliability of the electrical system as a whole.